2008
DOI: 10.1364/ao.47.001810
|View full text |Cite
|
Sign up to set email alerts
|

Detection of uranium in solids by using laser-induced breakdown spectroscopy combined with laser-induced fluorescence

Abstract: Detection of uranium in solids by using laser-induced breakdown spectroscopy has been investigated in combination with laser-induced fluorescence. An optical parametric oscillator wavelength-tunable laser was used to resonantly excite the uranium atoms and ions within the plasma plumes generated by a Q-switched Nd:YAG laser. Both atomic and ionic lines can be selected to detect their fluorescence lines. A uranium concentration of 462 ppm in a glass sample can be detected by using this technique at an excitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…We have recently applied the technique of CW two-dimensional fluorescence spectroscopy (2DFS) to measure the correlated absorption and emission properties of laser-produced plasmas in air 17 . In addition to enhancing emission intensity 18 , the high spectral resolution of 2DFS can more effectively isolate absorption from specific transitions, even in the presence of nearby absorption/emission lines 19 . Furthermore, LIF has a more favorable measurement geometry than LAS for standoff detection applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently applied the technique of CW two-dimensional fluorescence spectroscopy (2DFS) to measure the correlated absorption and emission properties of laser-produced plasmas in air 17 . In addition to enhancing emission intensity 18 , the high spectral resolution of 2DFS can more effectively isolate absorption from specific transitions, even in the presence of nearby absorption/emission lines 19 . Furthermore, LIF has a more favorable measurement geometry than LAS for standoff detection applications.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work on optical spectroscopy of laser-ablated uranium has been performed using a variety of uranium-containing solids, including uranium oxides 1215, 22 , uranium-doped glasses 3, 16, 18, 23, 24 , uranium ore 22, 25 , and uranium-containing soils 6, 26 . These samples contain a range of other elements as part of their sample matrix, which complicates interpretation of the optical spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Very high-resolution LIBS spectrometer was also employed for determining the isotopic composition of U and Pu [21][22][23]. Shen and Lu showed the applicability of uranium detection up to 462 ppm in glass samples by LIBS in combination with laser-induced fluorescence [24]. More recently, Jung et al demonstrated the applicability of Echelle spectrometer based LIBS system for the determination of U up to 5 wt % in normal glass samples prepared in the laboratory oven [25].…”
Section: Introductionmentioning
confidence: 99%
“…Information vitally important in the monitoring of nuclear processing and forensics are the isotope ratios of special nuclear material. The isotope ratio of elements can be determined by measuring the atomic line shift by laser absorption and laser fluorescence, which requires an ablative prestep [3][4][5][6][7]. LIBS can also measure the isotopic line shift as both Pietsch et al and Smith et al have demonstrated [8,9].…”
Section: Introductionmentioning
confidence: 99%